Iron Utilization in Marine Cyanobacteria and Eukaryotic Algae - Morrissey, Joe; Bowler, Chris (Frontiers in Microbiology, 2012)
Iron is essential for aerobic organisms. Additionally, photosynthetic organisms must maintain the iron-rich photosynthetic electron transport chain, which likely evolved in the iron-replete Proterozoic ocean. The subsequent rise in oxygen since those times has drastically decreased the levels of bioavailable iron, indicating that adaptations have been made to maintain sufficient cellular iron levels in the midst of scarcity. In combination with physiological studies, the recent sequencing of marine microorganism genomes and transcriptomes has begun to reveal the mechanisms of iron acquisition and utilization that allow marine microalgae to persist in iron-limited environments.